Identification of preferred sources of information for undertaking studies in the Faculty of Engineering Management at Poznan University of Technology - Wyrwicka, Magdalena K,; Mrugalska, Beata (Business, Management and Economics Engineering, 2015)
Since 2010 a survey has been conducted among first-year students about sources of information which influence the decision of undertaking field studies in Safety Engineering, Management Engineering and Logistics in the Faculty of Engineering Management at Poznan University of Technology. The goal of these analyses is both to assess the effectiveness of promotion and also show trends in the use of diverse channels of information transfer of studies. The results of the investigation show that internet promotion via university and faculty website plays the dominant role but also direct promotion, such as opinion of older friends, is crucial. Furthermore, from year to year the analyses indicate the significant increase of official media and reveal that the prospective students rely on a few sources of information simultaneously.